Simplified Tax Procedures in the New Tax Ordinance Act in Poland - Etel, Leonard; Popławski, Mariusz (Public Governance, Administration and Finances Law Review, 2018)
The purpose of this article is to indicate the need to simplify typical tax procedures but also to explain how it could be done. The discussed issues are based on proposed provisions provided in the draft of the New Tax Ordinance Act prepared by the General Tax Code Codification Committee. Efforts should be made to increase the efficiency of tax proceedings, which means, among others, the elimination of the overly extensive and formalized procedure for assessment of low tax amounts. At present, for example, proceedings regarding million zlotys tax amounts are carried out on identical terms as in the case of taxes amounting to several dozen PLN. The proposed new law will speed up the handling of many matters, but will also reduce the costs incurred in meeting all the existing procedural requirements. In addition, there should be no proceedings undertaken regarding tax amounts that are lower than the costs of obtaining them. The procedures for serving documents to taxpayers should be also simplified. Currently, they are very expensive. Additionally, they are often ineffective, which leads to the loss of significant tax revenues by the state. In addition, the process of granting individual tax reliefs should be simplified, especially in the context of local taxes. It should be enabled municipalities to independently decide on these entitlements and streamline the procedure for their granting.